Homeschooling and the unavoidable risks of education: reflections on the possibilities of schoolless education in the plural world from Arendt, Biesta and Savater (Práxis Educativa, 2020)
Faced with the growth of the theme of Homeschooling in the Brazilian political scenario and the presentation of Bills to regulate the practice, this paper intended, based on a theoretical investigation, to reflect on the possibilities of “schoolless education” in the contemporary world. It sought to understand, from Arendt, Biesta and Savater, what Education consists of and what is the character of the school. It reflected on the distinctions and educational roles of the private and public spheres and the place of school between them, as well as what effective education means. It concluded that, although the affirmations that homeschooling would have better academic performances could be confirmed, only the school can offer conditions for an effective Education, because only at school it is possible to create relatively safe opportunities for the contagion of what other is and for the adult insertion in the world.Keywords: Homeschooling. Private sphere. Public sphere.